Predatory Pricing in Buying and Selling Imported Products in E-Commerce According to the Perspective of Business Competition Law and Muamalah Fiqh - Kurlillah, Anis; Hisan, Syifaul; Tamam, Badrut (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
The presence of E-Commerce makes it easier to export and import goods without geographical boundaries, but it also gives rise to allegations of Predatory Pricing practices which are detrimental to other business actors and consumers. Predatory Pricing is a strategy of temporarily setting product prices below production costs or market prices in order to reduce competitors and gain market share. This suspicion arose because imported products were sold much cheaper than local products, as was the case at Fistyle and Biu.costore stores. However, this action needs to be proven by the Business Competition Supervisory Commission (KPPU). Problem Formulation 1) What are the indications of the implementation of Predatory Pricing by Fistyle and Biu.costore stores. 2) How is the legal review of Predatory Pricing practices by Fistyle stores and Biu.costore according to the Business Competition Law based on Law no. 5 of 1999. 3) What is the legal review of Predatory Pricing practices by Fistyle stores and Biu.costore according to Fiqh Muamalah. This article is empirical juridical research and the approach is statutory and conceptual. The data sources used are primary and secondary, data collection through interviews and observations and analysis using source and technical triangulation techniques. The research results show that the practice of Predatory Pricing is prohibited according to Article 20 of Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. This action is considered a violation if it meets the elements in Article 20. However, the Fistyle and Biu.costore stores were not proven to have violated this Article because they did not carry out Predatory Pricing. In Muamalah Fiqh, pricing in the market is expected not to exceed the prevailing market price, to maintain fairness and balance. The practices carried out by Fistyle stores include Siyasah al-Ighraq, because they cause losses to other business actors and consumers, such as selling defective goods and destroying market prices. Meanwhile, Biu.costore cannot yet be categorized as Siyasah al-Ighraq because it has just been established and there have been no complaints. Although both stores offer very low prices, not all actions considered Predatory Pricing are prohibited; Low prices can come from efficient and innovative business operations.